2016
DOI: 10.15405/epsbs.2016.05.02.1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences In Anxiety, Depression And Metacognition

Abstract: There are many gender differences relating to mental health issues and they concern all aspects: diagnosis, treatment and incidence. No research has been conducted to evaluates the role of metacognition on the basis of gender and its relation to other psychological constructs. This study had two primary goals. The first was to compare metacognitions by gender. The second goal was to explore the relations among the constructs of metacognitions, anxiety, depression, pathological worry, and obsessive-compulsive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
1
5
1
Order By: Relevance
“…41 Other factors, such as female gender were, as expected, good predictors of anxiety. 42,43 In contrast to other studies, 40,44 we found that higher education levels tend to be associated with higher anxiety. This result may be confounded by high intelligence quotient as Karpinski et al 45 have shown that higher intelligence is a risk factor for anxiety and other psychological disorders.…”
Section: Anxietycontrasting
confidence: 99%
See 1 more Smart Citation
“…41 Other factors, such as female gender were, as expected, good predictors of anxiety. 42,43 In contrast to other studies, 40,44 we found that higher education levels tend to be associated with higher anxiety. This result may be confounded by high intelligence quotient as Karpinski et al 45 have shown that higher intelligence is a risk factor for anxiety and other psychological disorders.…”
Section: Anxietycontrasting
confidence: 99%
“…Hypertension was associated with a 1.5‐point increase in the anxiety score ( P = 0.003), a relationship that is well known and studied . Other factors, such as female gender were, as expected, good predictors of anxiety . In contrast to other studies, we found that higher education levels tend to be associated with higher anxiety.…”
Section: Discussionsupporting
confidence: 51%
“…That is even in spite of the fact that validation studies in various languages recognized differences in metacognitive beliefs even in healthy participants [12][13][14]. In the last few years alterations in metacognition have not only been interpreted as characteristic markers for psychotic prodromes, but more generally as an important factor in inducing and aggravating psychiatric illness [33]. As previously discussed, there are increasing indications pointing towards the importance of metacognition in a broader aspect of psychologic functioning as well as psychiatric disease development and maintenance [33].…”
Section: K Original Article Discussionmentioning
confidence: 99%
“…In the last few years alterations in metacognition have not only been interpreted as characteristic markers for psychotic prodromes, but more generally as an important factor in inducing and aggravating psychiatric illness [33]. As previously discussed, there are increasing indications pointing towards the importance of metacognition in a broader aspect of psychologic functioning as well as psychiatric disease development and maintenance [33]. Alterations in metacognition are possibly decisive cognitive factors not only in psychotic episodes, but also in mood disorders and anxiety disorders [33].…”
Section: K Original Article Discussionmentioning
confidence: 99%
“…Regarding clinical group, empirical research in this area shows relationships between dysfunctional metacognitive beliefs and the following: generalized anxiety disorder (Wells & Carter 2001;Wells 2007), social phobia (Wells & Carter 2001;Wells 2007), panic disorder (Wells and Carter 2001;Wells 2007), obsessive-compulsive symptoms (Wells and Papageorgiou 1998), hallucination-prone subjects (Larøi, Van der Linden, & Marczewski, 2004), predisposition to hallucinations (García-Montes, Cangas, Pérez-Álvarez, Fidalgo, & Gutiérrez, 2006), anorexia nervosa (Cooper, Grocutt, Deepak, & Bailey, 2007), schizophrenic subjects with hallucinations (Perona-Garcelàn et al 2011), patients with severe auditory verbal hallucinations (van Oosterhout, Krabbendam, Smeets, & van der Gaag, 2012), distress associated with auditory verbal hallucinations (Hill, Varese, Jackons, & Linden, 2012), stress sensitization in individuals at ultra-high risk of developing psychosis (Palmier-Claus, Dunn, Taylor, Morrison, & Lewis, 2013), and outpatients with gastrointestinal disorders (Aszalos 2008; Lenzo, Buccheri, Sindorio, Belvedere, Fries, & Quattropani, 2013), and symptom severity in chronic fatigue syndrome (Maher-Edwards, Fernie, Murphy, Wells, & Spada, 2011).…”
Section: Responsibility Of the Conference Organization Committeementioning
confidence: 99%